ETHICS OF LIABILITY K.-O.APELY IN THE LANDSCAPES OF CONTRACTUALISM - Dmytro V. Usov (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
The purpose is to analyse comprehensively the work of the famous German philosopher K-O. Apel through the light of the urgent needs for a comprehensive study of modern contractualism and the development of new variants of philosophical anthropology. In this context to reveal April’s thesis that the main background for the possibility of understanding between people is the ideal communicative community and its attempts to discourse ethics, new, practical content. Methodology. In order to make a sequential analysis of the basic components and principles of ethical responsibility in K-O. Apel’s view of counteractualism the author uses genealogical, hermeneutic and comparative methods that allow to reconstruct Apel’s philosophy as the ethics of global responsibility and solidarity of communicative interaction under the conditions of global environmental and social crisis and the urgent need of vital combination of social contract idea, fairness and responsibility. Scientific novelty. The purpose of the article is clearly defined and productive methodological principles consistently enabled the author to find out that Apel perceives the source of social agreement in rational desire of each participant to obey voluntarily the relevant rules and procedures. And a true freedom and responsibility are based on the correlation of the rights and duties; respect them, which is more significant for the enforcement of their conventional or forced recognition. It is also investigated the attempt of K.-O. Apel to enable such an agreement and understanding between people, which would take into account the following important human virtues and aspirations, respect, justice and solidarity. And above all they are important as being the social and existential foundations for a new philosophical and anthropological discourse. It is consistently proved that in the context of substantial interest of justification was established the algorithms of universal values of modern philosophical anthropology, which will become the core of Apel’s responsible person. Excluding the ethical component of this or that agreement, the essence of democratic behaviour changes to rational behaviour of the participants and to the law validity of agreements belongs only the effectiveness in achieving the best interests of their members. It was reconstructed the memories of K.-O. Apel and Y. Habermas about the need and methodological importance of significance of epistemological (or methodological) solipsism of modern philosophy and its replacement by the concepts of "understanding", "agreement", "communication" within which even a single person can know and understand the world. Conclusions. An important feature of the latest philosophical theories, which include communication philosophy of K.-O. Apel is their organic belonging to the realm of discussion about the search of moral foundations of modern society where basic ethical guidelines and values must leave and eventually leave the sphere of private life, indicating that real attempts to overcome the fragmentation and dispersion of responsibility of the individual. It was exactly K.-O. Apel who stresses that collective irresponsibility should be replaced by collective responsibility.